“The Beloved Purple of Their Eyes: Inheriting Bessie Smith’s Politics of Sexuality” - Miquel-Baldellou, Marta (Miscelánea: A Journal of English and American Studies, 2007)
Bessie Smith has traditionally been regarded as The Empress of the Blues. Armed with a potent voice and a daring performance, she became one of the first and most popular African-American artists of all time. Through the lyrics of her songs, she underlined the difficulties many African-American women underwent at the time, focusing on their sorrows, their sexuality and the relationships they established with both males and other females. The politics of gender tackled in Bessie Smith’s songs are also often repeated in novels written by canonical African-American writers such as Zora Neale Huston, Alice Walker and Toni Morrison. Zora Neale Hurston was Bessie’s contemporary writer and met her during one of her journeys, while both Alice Walker and Toni Morrison acknowledged the influence Bessie Smith exerted over their writings. The aim of this article is to identify Bessie Smith’s politics of sexuality in Zora Neale Hurston’s Their Eyes Were Watching, Alice Walker’s The Colour Purple and Toni Morrison’s Beloved, in accordance with the new perspectives of Black Feminist Studies today
Keywords: Black feminism; Blues; Gender and sexuality; Bessie Smith; Zora Neale Hurston; Alice Walker; Toni Morrison